2018
DOI: 10.1007/s00737-018-0907-1
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status among female sex workers in Tabriz, Iran

Abstract: Female sex workers are a deprived part of Islamic communities. It is necessary for public health policy makers to have knowledge about their mental health status. This study aims to have an evaluation of mental health among female sex workers in Tabriz for the first time in northwest of Iran. In this cross-sectional study, 48 female sex workers who had accepted to be evaluated were included. Sociodemographic and general mental health statuses, using General Health Questionnaire (GHQ-28), were recorded. Those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The pooled prevalence of depression among FSWs from LMICs is 41.8% (95% CI 35.8%–48.0%). Seven studies reported on the prevalence of anxiety among FSWs [ 9 , 32 , 33 , 50 , 58 , 64 , 70 ], with 3 included in the meta-analysis ( Fig 3 ). The pooled prevalence of anxiety among FSWs from LMICs is 21.0% (95% CI 4.8%–58.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled prevalence of depression among FSWs from LMICs is 41.8% (95% CI 35.8%–48.0%). Seven studies reported on the prevalence of anxiety among FSWs [ 9 , 32 , 33 , 50 , 58 , 64 , 70 ], with 3 included in the meta-analysis ( Fig 3 ). The pooled prevalence of anxiety among FSWs from LMICs is 21.0% (95% CI 4.8%–58.4%).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled prevalence of psychological distress experienced by FSWs from LMICs was 40.8% (95% CI 20.7%-64.4%). Two studies examined mood disorders [70,74]. Only one study [74] was eligible for inclusion in a meta analysis and thus a pooled prevalence estimate is not available.…”
Section: Plos Medicinementioning
confidence: 99%
“…In fact, 19.9% of sex workers in Canada reported having anxiety [17]. Simons et al discovered, in a study conducted on 193 female sex workers in Zurich, that anxiety's effect on these women was 34% [55,56]. Similarly, a study conducted in Iran showed that 39% of sex workers suffered from anxiety, while these rates in Austria were 17% and reached 31% in Israel [56].…”
Section: Anxietymentioning
confidence: 99%
“…Simons et al discovered, in a study conducted on 193 female sex workers in Zurich, that anxiety's effect on these women was 34% [55,56]. Similarly, a study conducted in Iran showed that 39% of sex workers suffered from anxiety, while these rates in Austria were 17% and reached 31% in Israel [56]. Some female sex workers mentioned that they experienced neglect in their childhood and that carelessness influenced their personality development [57].…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation